The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.apsb.2018.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the biology of HER3 receptor as a therapeutic target in human cancer

Abstract: HER3 belongs to the human epidermal growth factor receptor (HER) family which also includes HER1/EGFR/erbB1, HER2/erbB2, and HER4/erbB4. As a unique member of the HER family, HER3 lacks or has little intrinsic tyrosine kinase activity. It frequently co-expresses and forms heterodimers with other receptor tyrosine kinases (RTKs) in cancer cells to activate oncogenic signaling, especially the PI-3K/Akt pathway and Src kinase. Elevated expression of HER3 has been observed in a wide variety of human cancers and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
89
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 107 publications
1
89
0
Order By: Relevance
“…Activation of c-Met upon ligation with its ligand hepatocyte growth factor bypasses EGFR inhibition by activating the JAK-STAT3, PI3K-Akt-mTOR and MAPK pathways, 23,24 while Her-3 might activate c-Met or EGFR without ligand binding by dimerizing with these growth factor receptors. 13,25 Moreover, previous study suggested that the coexistence of Met ad T790M mutation contributed to EGFR TKI resistance in advanced NSCLC. 26 These works indicated c-Met and Her-3 might serve as possible therapeutic target for the treatment of EGFR TKI resistant, metastatic or advanced-stage NSCLC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of c-Met upon ligation with its ligand hepatocyte growth factor bypasses EGFR inhibition by activating the JAK-STAT3, PI3K-Akt-mTOR and MAPK pathways, 23,24 while Her-3 might activate c-Met or EGFR without ligand binding by dimerizing with these growth factor receptors. 13,25 Moreover, previous study suggested that the coexistence of Met ad T790M mutation contributed to EGFR TKI resistance in advanced NSCLC. 26 These works indicated c-Met and Her-3 might serve as possible therapeutic target for the treatment of EGFR TKI resistant, metastatic or advanced-stage NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous researches have demonstrated that miR-148a would suppress the gene expression of ERBB3, 10 MET 11 and IGF1R 12 via directly interacting with the target sequences on the 3 0 untranslated regions (3 0 UTRs) of these genes' mRNAs, thus triggering gene silencing mediated by the RNA-induced silencing complex (RISC). Her-3, Insulin growth factor-1 receptor and c-Met proteins are three growth factor receptors encoded by these three genes, whose upregulation plays pivotal role in the development of EGFR TKI resistance in NSCLC, [13][14][15] and targeting these proteins has been suggested to improve the therapeutic effect of EGFR TKI against NSCLC. [16][17][18][19] The present research attempted to explore whether and how miR-148a would regulate NSCLC cells' resistance to EGFR TKI treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Co-expression of HER3 is, therefore, considered a cause for the development of therapy resistance, which has, for instance, been documented for the tyrosine kinase inhibitors (TKIs) lapatinib and gefitinib, targeting epidermal growth factor receptor (EGFR) and HER2 [6][7][8]. Thus, inhibition of HER3-mediated signaling might have potential to overcome therapy resistance [4,9] and monitoring of HER3 expression could, therefore, aid strategic decision making for cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Second, P2Y12 could regulate EGFR activation by promoting EGFR association with another member of the EGFR family, the human epidermal growth factor receptor 3 (HER3). Thus, inhibition of the purinergic receptor could reduce HER3 activation, and subsequently EGFR activation [19,43]. Third, P2Y12 could induce EGFR activation via Src, then the transactivated EGFR forms a multireceptor complex with P2Y12, leading to an increase in the downstream oncogenic signaling [44].…”
Section: Discussionmentioning
confidence: 99%